2014
DOI: 10.1539/joh.14-0034-oa
|View full text |Cite
|
Sign up to set email alerts
|

Female Breast Cancer and Electrical Manufacturing: Results of a Nested Case‐control Study

Abstract: Enrico ODDONE, et al.: Breast Cancer and Electrical Manufacturing Conclusions: Our results suggest an increased risk of breast cancer after exposure to chlorinated solvents among women employed in the electrical manufacturing industry. (J Occup Health 2014; 56: 369-378)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 25 publications
(27 reference statements)
0
8
0
Order By: Relevance
“… Helsinki Health Study High-Income ( Aittomäki et al, 2003 ) Longitudinal Role clarity, fairness, organizational climate Short sickness absence; long sickness absence; very long sickness absence Exposure-outcome among blue-collar women Among blue-collar women, the rate of short absence spells for those exposed to poor organizational climate were 1.6 times the rate of short absence spells for those with a favorable organizational climate (HR = 1.6, 95% CI 1.0–2.5). All employees of a forest industry corporation in Finland High-Income ( Väänänen et al, 2004 ) Longitudinal Race/ethnicity, age, education, occupation, shift worked, tenure, hourly rate of pay, full-time employment, having 2 jobs Lost-Worktime Injury or Illness Blue-collar women vs. other women C Among women, the odds of reporting a lost-worktime injury or illness were decreased among machine operators (OR = 0.73, 95% CI 0.38–1.41) and craftswomen (OR = 0.57 (0.24, 1.33) as compared with laborers. The rates of lost-worktime injury or illness were increased among machine operators (IRR = 2.41, 95% CI 0.86–6.74) and decreased among craftswomen (IRR = 0.58, 95% CI 0.19–1.78) as compared with laborers.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… Helsinki Health Study High-Income ( Aittomäki et al, 2003 ) Longitudinal Role clarity, fairness, organizational climate Short sickness absence; long sickness absence; very long sickness absence Exposure-outcome among blue-collar women Among blue-collar women, the rate of short absence spells for those exposed to poor organizational climate were 1.6 times the rate of short absence spells for those with a favorable organizational climate (HR = 1.6, 95% CI 1.0–2.5). All employees of a forest industry corporation in Finland High-Income ( Väänänen et al, 2004 ) Longitudinal Race/ethnicity, age, education, occupation, shift worked, tenure, hourly rate of pay, full-time employment, having 2 jobs Lost-Worktime Injury or Illness Blue-collar women vs. other women C Among women, the odds of reporting a lost-worktime injury or illness were decreased among machine operators (OR = 0.73, 95% CI 0.38–1.41) and craftswomen (OR = 0.57 (0.24, 1.33) as compared with laborers. The rates of lost-worktime injury or illness were increased among machine operators (IRR = 2.41, 95% CI 0.86–6.74) and decreased among craftswomen (IRR = 0.58, 95% CI 0.19–1.78) as compared with laborers.…”
Section: Resultsmentioning
confidence: 99%
“…By contrast, two studies found decreased likelihood of functional impairment in Mexican blue-collar women ( Guendelman and Silberg, 1993 ) and decreased odds of having a long-term condition, reduced activity days, or time off work among Australian blue-collar women ( Korda, Strazdins, Broom, & Lim, 2002 ) as compared with their respective counterparts in white-collar jobs. Only three studies considered determinants of disability and absenteeism among blue-collar women, and identify risk factors ranging from organizational climate ( Oddone et al, 2013 , Oddone et al, 2014 ) and work-family conflict ( Väänänen et al, 2008 ) to reduced heart rate reserve ( Gupta et al, 2014 ).…”
Section: Description Of Findings By Health Outcome Categorymentioning
confidence: 99%
“…Examples of toxic materials include photoactive chemicals, solvents, acids, and toxic gases. Chlorinated solvents used in electrical manufacturing plants have been suggested to be carcinogenic (Oddone et al, 2014). Renal and breast cancer risk in electrical manufacturing have also been reported in the United States and Italy (Karami et al, 2012;Oddone et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Organic solvents are ubiquitous in occupational settings where they may contribute to risks for carcinogenesis. Therefore several research groups investigated the effects of organic solvents on human breast carcinogens [103][104][105][106][107][108][109][110][111].…”
Section: Organic Solventsmentioning
confidence: 99%
“…Oddone et al [103] carried out a nested case-control study within a cohort of women employed in a large electrical manufacturing plant located in Lombardy in the Province of Milan. All incident cases during 2002 to 2009 of female breast cancer in individuals who worked at least a 1 year in the factory and resided in Lombardy, Italy, were selected, and controls were randomly sampled from all women who worked in the same plant and resided in Lombardy as of December 31, 2005.…”
Section: Organic Solventsmentioning
confidence: 99%